Cluster Analysis of Physiological Traits in F1-F2 Plants and Varieties Belonging to Phaseolus Vulgaris L. Species - Tursunova, Nilufar Muydinovna (American Journal of Botany and Bioengineering, 2024)
This article presents the results of cluster analysis of the physiological traits of Ғ1-Ғ2 plants obtained from original forms of Phaseolus vulgaris L. species and their hybridization. In our observations, we performed cluster analysis based on the parameters of physiological traits such as chlorophyll "a", "b", total chlorophyll, amount of carotenoids, transpiration rate, water storage properties of leaves, total water content of leaves. As a result, 4 cluster groups were revealed based on physiological traits, and the minimum and maximum Euclidean distance was found to be 0.1-12.0 units.